VD_FINDINFO Jug / 2011 / 127 vom 15. März 2011 - VD Tribunal cantonal (2011)
CRÉANCE, PRÉTENTION DE DROIT PUBLIC, RÉSEAU DE CÂBLES, DROIT DE DIFFUSION, RETRANSMISSION PAR SATELLITE | 150bis CP, 23 LCD, 5c LCD, 67 LDA, 69 LDA, 69a LDA